2016
DOI: 10.1016/j.healthpol.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Health benefit assessment of pharmaceuticals: An international comparison of decisions from Germany, England, Scotland and Australia

Abstract: We show that the FJC - an agency relatively new in structurally assessing the health benefit of pharmaceuticals - deviates considerably in decisions compared to other HTA agencies. Our study also reveals that the FJC tends to appraise stricter than NICE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…High-level comparisons of review processes between jurisdictions show that drug reimbursement decisions are important across healthcare systems yet vary in the structures and decision criteria used [ 16 ], process indicators [ 17 , 18 ] and resulting recommendations [ 19 21 ]. Variations are attributed to general differences between health systems [ 19 , 22 ] and insufficient economic evidence [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-level comparisons of review processes between jurisdictions show that drug reimbursement decisions are important across healthcare systems yet vary in the structures and decision criteria used [ 16 ], process indicators [ 17 , 18 ] and resulting recommendations [ 19 21 ]. Variations are attributed to general differences between health systems [ 19 , 22 ] and insufficient economic evidence [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning Health Technology Assessment (HTA), some authors compared various agencies from different countries. For example, Fischer analysed whether decisions of the FJC deviate from judgments of the UK National Institute for Health and Care Excellence (NICE), the Scottish Medicines Consortium (SMC) and the Australian Pharmaceutical Benefits Advisory Committee (PBAC) . Fischer concluded that FJC considerably deviates in its outcomes from established HTA agencies and that FJC tends to appraise stricter regarding comparative effectiveness than NICE.…”
Section: Discussionmentioning
confidence: 99%
“…The timeline of the NICE HTA process, independent from AWMSG, has been considered previously. Single technology appraisals—a process appraising a single product with a single indication—takes NICE approximately 9–12 months to complete [ 41 ]. However, there is variability throughout the years; for example, in 2009, the median time to publication was 8 months (range 4–38 months), but in 2010 the median time was 29 months (range 4–30 months) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%